Expression of novel isoforms of carnitine palmitoyltransferase I (CPT-1) generated by alternative splicing of the CPT-ibeta gene. - Yu, G S (1998)
Carnitine palmitoyltransferase I (CPT-I) catalyses the rate-determining step in mitochondrial fatty acid beta-oxidation. The enzyme has two cognate structural genes that are preferentially expressed in liver (alpha) or fat and muscle (beta). We hypothesized the existence of additional isoforms in heart to account for unique kinetic characteristics of enzyme activity in this tissue. Hybridization and PCR screening of a human cardiac cDNA library revealed the expression of two novel CPT-I isoforms generated by alternative splicing of the CPT-Ibeta transcript, in addition to the beta and alpha cDNA species previously described. Ribonuclease protection and reverse transcriptase-mediated PCR assays confirmed the presence of mRNA species of each splicing variant in heart, skeletal muscle and liver, with differing relative concentrations in the tissues. The novel splicing variants omit exons or utilize a cryptic splice donor site within an exon. Deduced polypeptide sequences of the novel enzymes include omissions in the region of putative membrane-spanning and malonyl-CoA regulatory domains compared with the previously described CPT-Is, implying that the encoded enzymes will exhibit unique features with respect to outer mitochondrial membrane topology and response to physiological and pharmacological inhibitors.